Genome Sequences of the Biotechnologically Important Bacillus megaterium Strains QM B1551 and DSM319 - Eppinger, Mark (American Society for Microbiology, 2011)
Bacillus megaterium is deep-rooted in the Bacillus phylogeny, making it an evolutionarily key species and of particular importance in understanding genome evolution, dynamics, and plasticity in the bacilli. B. megaterium is a commercially available, nonpathogenic host for the biotechnological production of several substances, including vitamin B(12), penicillin acylase, and amylases. Here, we report the analysis of the first complete genome sequences of two important B. megaterium strains, the plasmidless strain DSM319 and QM B1551, which harbors seven indigenous plasmids. The 5.1-Mbp chromosome carries approximately 5,300 genes, while QM B1551 plasmids represent a combined 417 kb and 523 genes, one of the largest plasmid arrays sequenced in a single bacterial strain. We have documented extensive gene transfer between the plasmids and the chromosome. Each strain carries roughly 300 strain-specific chromosomal genes that account for differences in their experimentally confirmed phenotypes. B. megaterium is able to synthesize vitamin B(12) through an oxygen-independent adenosylcobalamin pathway, which together with other key energetic and metabolic pathways has now been fully reconstructed. Other novel genes include a second ftsZ gene, which may be responsible for the large cell size of members of this species, as well as genes for gas vesicles, a second β-galactosidase gene, and most but not all of the genes needed for genetic competence. Comprehensive analyses of the global Bacillus gene pool showed that only an asymmetric region around the origin of replication was syntenic across the genus. This appears to be a characteristic feature of the Bacillus spp. genome architecture and may be key to their sporulating lifestyle.